2007
DOI: 10.1255/ejms.891
|View full text |Cite
|
Sign up to set email alerts
|

Negative Matrix-Assisted Laser Desorption/Ionization Time-of-Flight/Time-of-Flight Tandem Mass Spectrometry Fragmentation of Synthetic Analogs of the O-Specific Polysaccharide of Vibrio Cholerae O:1 in the Presence of Anionic Dopants

Abstract: Oligosaccharides (tri- to hexamers) that represent terminal epitopes of O-antigens of Vibrio cholerae O:1, serotypes Ogawa and Inaba, have been studied by negative matrix-assisted laser desorption/ionization time of flight/time-of-flight mass spectrometry (MALDI ToF/ToF MS). The [M - H(+)](-) ions are formed after expulsion of a proton from molecules studied under condition of MALDI MS analysis in the negative mode. Several ammonium salts (chloride, nitrate, hydrogencarbonate and hydrogensulfate) were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Alternatively, some investigators have adducted carbohydrates with anions such as chloride and sulfate and observed strong signals. Chmelík et al (2007) have investigated the addition of ammonium chloride, nitrate, hydrogen-carbonate and hydrogen-sulfate to DHB or THAP and report that hydrogen-carbonate appears to produce the most intense [M þ H] À ions without adduct formation. The most abundant adducts were formed with nitrate ([M þ NO 3 ] À ).…”
Section: G Matrices Producing Negative Ions From Neutral Glycansmentioning
confidence: 99%
“…Alternatively, some investigators have adducted carbohydrates with anions such as chloride and sulfate and observed strong signals. Chmelík et al (2007) have investigated the addition of ammonium chloride, nitrate, hydrogen-carbonate and hydrogen-sulfate to DHB or THAP and report that hydrogen-carbonate appears to produce the most intense [M þ H] À ions without adduct formation. The most abundant adducts were formed with nitrate ([M þ NO 3 ] À ).…”
Section: G Matrices Producing Negative Ions From Neutral Glycansmentioning
confidence: 99%
“…Saccharides and oligonucleotides are usually analyzed under negative ionization conditions [ 8 , 9 ]. We obtained the IG20 glycoside as a unique final product of a chemical synthesis process [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…13 For fragmentation analysis of OSP of V. cholerae O1, negative matrix-assisted laser desorption ionization (MALDI)-time of flight (TOF)/TOF and positive and negative ESI-MS/ MS analyzes were used. 14,15,16 MALDI-TOF/TOF and ESI-MS/MS analyzes were also used for fragmentation analysis of bacterial LPSs, lipooligosaccharides and O-antigens of other bacteria, such as Neisseria meningitidis, Escherichia coli or Vibrio fischeri. [17][18][19][20] In this work, structural and fragmentation analyzes of the OSP and core part of LPS isolated from V. cholerae O139 were performed by i.)…”
Section: Introductionmentioning
confidence: 99%